A University-Stakeholder Collaborative Approach to Designing Early Childhood Mentor Teacher Training - Edith Nicolas; Cristina Guarrella; Parian Madanipour (International Journal of Qualitative Methods)
This paper aims to investigate the relationship between participative approaches and knowledge construction by showing in what ways community engagement in academic research can inform the design and development of professional learning resources. Mentor teachers play a key role in supporting pre-service teachers’ learning and development in the context of Initial Teacher Education practicum. While the complexity of this role is highlighted in the literature, teachers are rarely provided with the opportunity to engage in professional learning to support their mentoring practice. We engaged with a group of Early Childhood Education and Care professionals and pre-service teachers to identify mentor teachers’ professional learning needs and design, develop and deliver a range of training resources to support mentoring practice. Our research marks a shift from the traditionally top-down approach to developing Initial Teacher Education programs, towards shared leadership where university academics’ and education professionals’ expertise are positioned on an equal footing. Semi-structured interviews first gathered data on the challenges and strengths of the practicum experience from both mentors and pre-service teachers. This data informed the design and development of resources that were further reviewed and refined through iterative loops of feedback. These dynamic processes of information sharing resulted in a layering of knowledges that led to the creation of genuinely contextual professional learning resources. Given the crucial importance of Early Childhood Education and Care in relation to children’s learning and development, the value of participative methodologies in professional learning as well as the critical role played by mentors in quality initial teacher training, there is a critical lack of research on the topic in the Early Childhood Education literature. This study makes an essential contribution to understanding how Early Childhood Education and Care community engagement can better equip educators and institutions to provide high-quality early childhood education.